ANALISIS PERBANDINGAN VULNERABILITY SCANNING PADA WEBSITE DVWA MENGGUNAKAN OWASP NIKTO DAN BURPSUITE - Ni Putu Ana Rainita; Anak Agung Istri Callysta Athalia; Made Diva Putera Ananta; I Ketut Pratista Tri Pramana; Gede Arna Jude Saskara; I Made Edy Listartha (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
Information technology from time to time is growing rapidly and has become part of human life in this modern era, with these developments, websites have an important role, however, existing developments also have an impact on the security of a website, testing web servers is very important. important thing to do, this test aims to test whether the web server is safe or not from the crimes of hackers. Appropriate methods and techniques are needed to see possible vulnerabilities in components, libraries and systems that underlie web applications used in anticipating this, OWASP, Nikto, and Burp Suite tools can be used to test website security vulnerabilities. Each tool has differences in terms of speed or duration, results, or scanned objects. The research objective of this article is how to analyze a comparison of tools in testing website security vulnerabilities. Therefore, the results of detection or analysis of website vulnerabilities are then compared based on scanned objects, duration, and results to then suggest tools that are effective and efficient in their use.